The relation between blowing pressure and blowing frequency in clarinet playing - Bak, Niels; Dømler, Preben (Annual Report of the Institute of Phonetics University of Copenhagen, 2022)
Different opinions on the relation between blowing pressure and blowing frequency in clarinet playing provide the background for the investigations presented in this paper. By employing mechanical blowing and a newly developed artificial embouchure, test results have been obtained which show that the correlation between blowing pressure and blowing frequency is positive for all notes in the low register of the clarinet (the chalumeau register) when all other parameters are kept constant.